Nonaqueous electrolyte secondary battery

By using a filler layer composed of inorganic particles and resin particles in the spacer of the nonaqueous electrolyte secondary battery, the problems of electrode deformation and insufficient liquid permeability are solved, the stability and efficient permeability of the electrode plate are achieved, and the stability and efficiency permeability of the electrode are improved. Battery safety and production efficiency.

CN119156738APending Publication Date: 2024-12-17PANASONIC ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041453.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-22
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In a nonaqueous electrolyte secondary battery, the charge and discharge cycle of the electrode body causes the plate to deform, which may cause internal short circuits. The prior art has failed to effectively improve liquid permeability, affecting the safety and productivity of the secondary battery.

Method used

A spacer with a base layer and a filler layer is used. The filler layer contains inorganic particles and resin particles with an average particle size larger than that of inorganic particles. The resin particle forming convex portion protrudes from the inorganic particle layer and is detected in a 100μm x 100μm area by scanning electron microscope. There are 10 to 35 convex resin particles to enhance the liquid permeability and pressure resistance of the filler layer.

Benefits of technology

Effectively suppress plate deformation, while improving liquid permeability, and improving the safety and productivity of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156738A_ABST
    Figure CN119156738A_ABST
Patent Text Reader

Abstract

Provided is a nonaqueous electrolyte secondary battery in which liquid permeability is improved while suppressing deformation of an electrode plate. A nonaqueous electrolyte secondary battery according to one embodiment of the present invention is provided with an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, an electrolyte solution, and an outer can housing the electrode body and the electrolyte solution, the separator having a base material layer and a filler layer formed on at least one surface of the base material layer, the filler layer contains inorganic particles and resin particles having a larger average particle diameter than the inorganic particles, and has protrusions formed from the resin particles, the protrusions protruding from the inorganic particle layer, and the inorganic particle layer is a layer formed from the inorganic particles other than the protrusions in the filler layer. When the surface of the filler layer is observed with a scanning electron microscope, 10-35 resin particles forming the protrusions are detected in a 100 [mu] m * 100 [mu] m region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-aqueous electrolyte secondary battery. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries have been widely used as secondary batteries with high output power and high energy density. In non-aqueous electrolyte secondary batteries, lithium ions and the like are moved between a pair of electrode plates (positive electrode and negative electrode) via an electrolyte to perform charging and discharging. In the electrode body, the positive electrode and the negative electrode are oppositely disposed with a separator sandwiched therebetween, and the separator separates the positive electrode and the negative electrode from each other. The separator sometimes has a filler layer on the surface of a substrate layer composed of a porous polyolefin or the like for the purpose of improving heat resistance.

[0003] Patent document 1 discloses the following technology: in a soft-pack type secondary battery, two polymers with different particle sizes are contained in the packing layer opposite to the negative electrode, so that the surface of the packing layer is uneven. The soft-pack type secondary battery has flexibility and may be deformed due to the expansion and contraction of the electrode body during charging and discharging. Patent document 1 states that by making the surface of the packing layer uneven to generate voids, the increase in the thickness of the electrode body can be suppressed by allowing the voids to absorb the expansion of the negative electrode during charging.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-501453 Summary of the invention

[0007] However, in a non-aqueous electrolyte secondary battery in which the electrode body is housed in a metal outer packaging body, when the electrode body expands with the charge and discharge cycle, pressure is applied to the electrode body from the outer packaging body, and there is a case where the pole plate is deformed to produce bending of the pole plate. Since pole plate deformation may become a cause of internal short circuit, suppressing pole plate deformation is an important issue. In addition, the spacer has the function of retaining the electrolyte, and from the perspective of improving the productivity of the secondary battery, it is required to improve the liquid permeability. The technology disclosed in Patent Document 1 has not been studied for suppressing pole plate deformation and improving liquid permeability, and there is still room for improvement.

[0008] An object of the present invention is to provide a non-aqueous electrolyte secondary battery having improved liquid permeability while suppressing deformation of an electrode plate.

[0009] A non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises an electrode body formed by winding a positive electrode and a negative electrode with a separator sandwiched therebetween, an electrolyte, and an outer packaging can for containing the electrode body and the electrolyte, the separator having a substrate layer and a filler layer formed on at least one surface of the substrate layer, the filler layer comprising inorganic particles and resin particles having an average particle size greater than that of the inorganic particles, the convexities protruding from the inorganic particle layer, the inorganic particle layer being a layer formed of inorganic particles other than the convexities in the filler layer, and when the surface of the filler layer is observed using a scanning electron microscope, 10 to 35 resin particles forming the convexities are detected in an area of ​​100 μm×100 μm.

[0010] According to the nonaqueous electrolyte secondary battery of the present invention, it is possible to improve liquid permeability while suppressing deformation of the electrode plate, thereby improving the safety and productivity of the nonaqueous electrolyte secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery as an example of an embodiment.

[0012] Figure 2 It is a cross-sectional view of a spacer as an example of an embodiment.

[0013] Figure 3 It is a diagram for explaining a method for evaluating deformation of an electrode plate. DETAILED DESCRIPTION

[0014] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention will be described in detail with reference to the accompanying drawings. Although a cylindrical secondary battery in which an electrode body is contained in a cylindrical outer packaging can is exemplified below, the outer packaging can is not limited to a cylindrical shape, and may be, for example, square, button-shaped, etc. It should be noted that in the following description, specific shapes, materials, numerical values, directions, etc. are examples for facilitating the understanding of the present invention, and may be appropriately changed to match the specifications of the non-aqueous electrolyte secondary battery. In addition, in the following description, in the case of including a plurality of embodiments and variations, it is initially envisioned that their characteristic parts are appropriately combined for use.

[0015] Figure 1 It is a longitudinal cross-sectional view of a cylindrical secondary battery 10 as an example of the embodiment. Figure 1 The cylindrical secondary battery 10 shown contains an electrode body 14 and an electrolyte (not shown) in an outer can 15. It should be noted that, for the convenience of description, the direction along the axial direction of the outer can 15 is defined as "longitudinal or up-down direction", the sealing body 16 side is defined as "up", and the bottom side of the outer can 15 is defined as "down".

[0016] As the non-aqueous solvent (organic solvent) of the electrolyte, carbonates, lactones, ethers, ketones, esters, etc. can be used, and these solvents can be mixed and used in two or more kinds. In the case of mixing and using two or more solvents, it is preferred to use a mixed solvent containing cyclic carbonates and chain carbonates. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as cyclic carbonates, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), etc. can be used as chain carbonates. As esters, carbonates such as methyl acetate (MA) and methyl propionate (MP) are preferably used. The non-aqueous solvent can contain a halogen substitute in which at least a portion of the hydrogen atoms of these solvents are replaced by halogen atoms such as fluorine. As a halogen substitute, for example, fluoroethylene carbonate (FEC) and fluoromethyl propionate (FMP), etc. are preferably used. As the electrolyte salt of the electrolyte solution, LiPF6, LiBF4, LiCF3SO3, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, etc. and mixtures thereof can be used. The amount of the electrolyte salt dissolved in the non-aqueous solvent is, for example, 0.5 mol / L to 2.0 mol / L.

[0017] The electrode body 14 has a wound structure in which a strip-shaped positive electrode 11 and a strip-shaped negative electrode 12 are wound with a separator 13 interposed therebetween. The positive electrode 11, the negative electrode 12, and the separator 13 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by winding into a spiral shape. In the electrode body 14, the positive electrode 11, the negative electrode 12, and the separator 13 are wound, for example, 10 to 30 times. In order to prevent the precipitation of lithium, the negative electrode 12 is formed with a size one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction (short side direction). The separator 13 is formed with a size one circle larger than the positive electrode 11 and the negative electrode 12, and two sheets are arranged in a manner of sandwiching the positive electrode 11. The positive electrode lead 19 is connected to the approximately center of the length direction of the positive electrode 11 by welding, and the negative electrode lead 20 is connected to the inner end of the winding of the negative electrode 12 by welding.

[0018] Insulating plates 17 and 18 are disposed above and below the electrode body 14 , respectively. Figure 1In the example shown, the positive lead 19 extends toward the sealing body 16 through the through hole of the insulating plate 17 and is connected to the lower surface of the filter 22 of the sealing body 16 by welding or the like. In the secondary battery 10, the cover 26, which is the top plate of the sealing body 16 and is electrically connected to the filter 22, becomes the positive terminal. On the other hand, the negative lead 20 extends toward the bottom side of the outer packaging can 15 through the through hole of the insulating plate 18 and is connected to the bottom inner surface of the outer packaging can 15 by welding or the like. In the secondary battery 10, the outer packaging can 15 becomes the negative terminal. It should be noted that when the negative lead 20 is arranged at the outer end of the winding, the negative lead 20 extends toward the bottom side of the outer packaging can 15 through the outer side of the insulating plate 18 and is welded to the bottom inner surface of the outer packaging can 15.

[0019] As described above, the outer can 15 is a metal container in a cylindrical shape with a bottom and an opening on one side in the axial direction. A gasket 27 is provided between the outer can 15 and the sealing body 16 to ensure the airtightness of the battery interior and the insulation between the outer can 15 and the sealing body 16. The outer can 15 is formed with a groove 21 formed by a part of the side portion bulging inward to support the sealing body 16. The groove 21 is preferably formed in an annular shape along the circumferential direction of the outer can 15, and the sealing body 16 is supported by its upper surface. The sealing body 16 is fixed to the upper part of the outer can 15 by using the groove 21 and the open end of the outer can 15 that is caulked to the sealing body 16.

[0020] The sealing body 16 has a structure in which a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25 and a cover 26 are stacked in order from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected at their respective central portions, and an insulating member 24 is sandwiched between their respective peripheral portions. When an abnormality occurs in the battery and the internal pressure rises, the lower valve body 23 is deformed and broken in a manner that pushes the upper valve body 25 toward the cover 26 side, thereby blocking the current path between the lower valve body 23 and the upper valve body 25. When the internal pressure rises further, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cover 26.

[0021] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , particularly the separator 13 , will be described in detail.

[0022] [positive electrode]

[0023] The positive electrode 11 includes a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode current collector can be made of a foil of a metal such as aluminum that is stable in the potential range of the positive electrode, or a film having the metal disposed on the surface. The thickness of the positive electrode current collector is, for example, 10 μm to 30 μm.

[0024] The positive electrode mixture layer is preferably formed on both sides of the positive electrode collector. The thickness of the positive electrode mixture layer is, for example, 10 μm to 150 μm for one side of the positive electrode collector. The positive electrode mixture layer, for example, includes a positive electrode active material, a conductive agent, and a binder. For example, a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, a binder, etc. is applied to both sides of the positive electrode collector, and after the coating is dried, the coating is rolled using a roller or the like, thereby making a positive electrode.

[0025] Examples of the positive electrode active material contained in the positive electrode mixture layer include lithium transition metal composite oxides containing transition metal elements such as Co, Mn, and Ni. For example, lithium transition metal composite oxides are Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4、Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). These may be used alone or in combination of two or more.

[0026] In order to realize a high capacity of a non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains a lithium nickel composite oxide. Examples of the lithium nickel composite oxide include Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3), etc. The higher the Ni content of the lithium nickel composite oxide, the higher the capacity.

[0027] Examples of the conductive agent contained in the positive electrode mixture layer include carbon black (CB), acetylene black (AB), Ketjen black, carbon nanotubes (CNT), graphene, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0028] Examples of the binder contained in the positive electrode mixture layer include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0029] [negative electrode]

[0030] The negative electrode 12 includes a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode current collector can be made of a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface. The thickness of the negative electrode current collector is, for example, 5 μm to 30 μm.

[0031] The negative electrode mixture layer is preferably formed on both sides of the negative electrode collector. The thickness of the negative electrode mixture layer is, for example, 10 μm to 150 μm for one side of the negative electrode collector. The negative electrode mixture layer, for example, contains a negative electrode active material and a binder. For example, a negative electrode mixture slurry containing a negative electrode active material, a binder, etc. is applied to both sides of the negative electrode collector, and after the coating is dried, the coating is rolled using a roller or the like, thereby making a negative electrode.

[0032] The negative electrode active material contained in the negative electrode mixture layer is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and generally a carbon material such as graphite is used. The graphite can be any of natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphites such as graphitized mesophase carbon microbeads.

[0033] As the negative electrode active material, metals such as Si and Sn that are alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can also be used. x (0.5≤x≤1.6) Si-containing compounds, or Li 2y SiO (2+y) A Si-containing compound represented by (0<y<2) in which Si fine particles are dispersed in a lithium silicate phase is used in combination with graphite.

[0034] Since the Si-containing compound has a large expansion and contraction rate due to battery charge and discharge, the plate is easily deformed when the negative electrode 12 contains the Si-containing compound. Therefore, when the negative electrode 12 contains the Si-containing compound, the effect of the separator 13 described below is significant.

[0035] Examples of the binder contained in the negative electrode mixture layer include styrene butadiene rubber (SBR), acrylonitrile butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (PAA-Na, PAA-K, etc., and partially neutralized salt), polyvinyl alcohol (PVA), etc. These may be used alone or in combination of two or more.

[0036] [Spacer]

[0037] The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other, and prevents the positive electrode 11 and the negative electrode 12 from contacting each other and causing a short circuit. Figure 2 It is a cross-sectional view of the spacer 13 as an example of embodiment. Figure 2 In the example shown, the positive electrode 11 is arranged on the upper side of the separator 13 , and the negative electrode 12 is arranged on the lower side.

[0038] like Figure 2 As shown, the separator 13 includes a substrate layer 13a and a filler layer 13b formed on at least one surface of the substrate layer 13a. In this embodiment, the filler layer 13b is opposite to the positive electrode 11, and the substrate layer 13a is opposite to the negative electrode 12. It should be noted that this example is not limited to the filler layer 13b and the negative electrode 12 may be opposite to the substrate layer 13a and the positive electrode 11. In addition, the separator 13 may also have filler layers 13b on both sides of the substrate layer 13a.

[0039] As the substrate layer 13a, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the substrate layer 13a is not particularly limited, but examples thereof include polyolefins such as polyethylene, polypropylene, copolymers of polyethylene and α-olefins, acrylic resins, polystyrene, polyesters, cellulose, polyimides, polyphenylene sulfide, polyetheretherketone, fluororesins, etc. The substrate layer 13a may be a single-layer structure or a multi-layer structure. The thickness of the substrate layer 13a is preferably 3 μm to 20 μm, more preferably 5 μm to 15 μm.

[0040] The filler layer 13b includes inorganic particles 30 and resin particles 32 having an average particle size larger than that of the inorganic particles 30. In addition, the filler layer 13b has convex portions 32a formed by the resin particles 32, and the convex portions 32a protrude from an inorganic particle layer 34 formed by the inorganic particles 30 in the filler layer 13b. The inorganic particle layer 34 is a layer formed by the aggregation of the inorganic particles 30, and is formed in the region of the filler layer 13b excluding the convex portions 32a. Figure 2 In the example, the inorganic particles 30 are stacked in approximately two layers in the thickness direction of the separator 13 . However, the present invention is not limited to this example. The inorganic particles 30 may be stacked in only one layer or in two or more layers in the thickness direction of the separator 13 .

[0041] like Figure 2 As shown, the particle diameter d of the resin particles 32 in the thickness direction of the spacer 13 is larger than the thickness t of the inorganic particle layer 34. As a result, the upper part of the resin particles 32 forming the convex portion 32a protrudes from the inorganic particle layer 34. The resin particles 32 may also be in contact with the substrate layer 13a. The cross-section of the resin particles 32 may be circular or elliptical.

[0042] The average particle size (D50) of the resin particles 32 is preferably 1 μm to 10 μm larger than the thickness t of the inorganic particle layer 34. If the difference between the D50 of the resin particles 32 and the thickness t of the inorganic particle layer 34 is within this range, the effect of suppressing plate deformation and improving liquid permeability brought about by the spacer 13 is more significant. The D50 of the inorganic particles 30 is, for example, 0.3 μm to 0.8 μm. In this specification, the average particle size (D50) means the particle size at which the accumulation of frequencies in the volume-based particle size distribution reaches 50% from the smaller particle size, and is also called the median diameter. The particle size distribution of the inorganic particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bel) with water as the dispersion medium.

[0043] When the surface of the filler layer 13b is observed using a scanning electron microscope (SEM, such as SU8220 manufactured by Hitachi High-Tech), 10 to 35 resin particles 32 forming the convex portion 32a are detected in an area of ​​100 μm×100 μm. As a result, the internal stress generated by the expansion and contraction of the positive electrode 11 and the negative electrode 12 during the charge and discharge of the secondary battery 10 can be alleviated, thereby suppressing the deformation of the electrode plate. Here, the so-called electrode plate deformation refers to the bending of at least one of the pair of electrode plates (positive electrode 11 and negative electrode 12).

[0044] If the number of resin particles forming the convex portion 32a detected is less than 10, the effect of suppressing plate deformation will not be fully achieved. In addition, if the number of resin particles forming the convex portion 32a detected is more than 35, the liquid permeability will not be fully improved.

[0045] The convex portion 32a may be, for example, large enough to be detected by SEM observation of the surface of the filler layer 13b at a magnification of 1000 times. A 100 μm×100 μm area on the surface of the filler layer 13b is observed, and the number of resin particles 32 forming the convex portion 32a is counted. Three different areas are observed, and the average value of the number detected in each area is set as the number of resin particles 32 forming the convex portion 32a per unit predetermined area (100 μm×100 μm).

[0046] As the material of the resin particles 32, for example, there can be cited acrylic resins containing ethylenically unsaturated carboxylic acid alkyl esters such as methyl acrylate, butyl acrylate, ethyl acrylate, and 2-ethylhexyl acrylate, resins containing cyano-containing ethylenically unsaturated monomers such as acrylonitrile, resins containing ethylenically unsaturated carboxylic acids and their salts such as acrylic acid, methacrylic acid, and maleic acid, and the like.

[0047] The resin particles 32 have adhesion to the positive electrode 11, and in the secondary battery 10, the resin particles 32 are preferably bonded to the positive electrode. By bonding the resin particles 32 to the positive electrode 11, when the electrode body 14 expands due to charge and discharge, the effect of suppressing the internal stress of the electrode body 14 is more significant. The resin particles 32 show adhesion to the positive electrode 11 when retaining an electrolyte, for example.

[0048] Examples of the inorganic particles 30 include metal oxide particles, metal nitride particles, metal fluoride particles, and metal carbide particles. Examples of metal oxide particles include aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, and manganese oxide. Examples of metal nitride particles include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluoride particles include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbide particles include silicon carbide, boron carbide, titanium carbide, and tungsten carbide. In addition, the inorganic particles 30 may also be zeolite (M 2 / n O·Al2O3·xSiO2·yH2O, M is a metal element, n is the valence of M, x≥2, y≥0) and other porous aluminosilicates, talc (Mg3Si4O 10 (OH)2) and other layered silicates, barium titanate (BaTiO3), strontium titanate (SrTiO3) and other minerals, etc. These may be used alone or in combination of two or more.

[0049] The filler layer 13b may further include a binder. The binder has the function of bonding the inorganic particles 30 and the resin particles 32 as fillers to each other and to the filler and the substrate layer. The binder is preferably a polymer material, for example, fluorine resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide resins, polyamide resins, acrylic resins, polyolefin resins, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. They can be used alone or in combination of two or more.

[0050] In the filler layer 13 b , when the content of the inorganic particles 30 is 100 parts by mass, the content of the resin particles 32 is, for example, 1 to 10 parts by mass, and the content of the binder is, for example, 1 to 10 parts by mass.

[0051] Example

[0052] Hereinafter, the present invention will be further described using examples; however, the present invention is not limited to these examples.

[0053] <Example>

[0054] [Production of positive electrode]

[0055] As the positive electrode active material, LiNi 0.88 Co 0.09 Al 0.03 Lithium nickel cobalt oxide containing aluminum represented by O2. 100 parts by mass of a positive electrode active material, 1 part by mass of acetylene black (AB) and 0.9 parts by mass of polyvinylidene fluoride (PVDF) are mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is added to prepare a positive electrode mixture slurry. Then, the positive electrode mixture slurry is applied to both sides of a strip-shaped positive electrode collector made of aluminum foil with a thickness of 15 μm, and after drying, it is rolled and cut into a specified electrode plate size to produce a positive electrode with a positive electrode mixture layer formed on both sides of the positive electrode collector. In the approximate center of the longitudinal direction of the positive electrode, a positive electrode exposure portion is provided where there is no mixture layer and the surface of the collector is exposed, and an aluminum positive electrode lead is welded to the positive electrode exposure portion.

[0056] [Production of negative electrode]

[0057] 95 parts by mass of graphite, 5 parts by mass of Si oxide (SiO), 1 part by mass of sodium carboxymethyl cellulose (CMC-Na) and 1 part by mass of styrene butadiene rubber (SBR) were mixed and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Then, the negative electrode mixture slurry was applied to both sides of a strip-shaped negative electrode collector made of 8 μm thick copper foil, dried, rolled, and cut into a specified electrode plate size to produce a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode collector. At the inner end of the winding of the negative electrode, a negative electrode exposure portion where the mixture layer does not exist and the collector surface is exposed is provided, and a nickel negative electrode lead is welded to the negative electrode exposure portion.

[0058] [Making spacers]

[0059] As the substrate layer, a porous substrate made of polyethylene with a thickness of 12 μm was used. Alumina (α-Al2O3) particles with an average particle size (D50) of 0.7 μm as inorganic particles, acrylic resin particles with a D50 of 4 μm as resin particles, and an acrylic ester binder emulsion were mixed at a solid content mass ratio of 100:2:3, and then an appropriate amount of water was added to make the solid content concentration 10% by mass to prepare a dispersion. The dispersion was applied to the entire surface area of ​​the porous substrate as the substrate layer using a micro gravure coater. Thereafter, the coating was dried by heating in an oven at 50°C for 4 hours to form a filler layer having convex portions obtained by protruding acrylic resin particles from the surface of the inorganic particle layer with a thickness of 3 μm formed by α-Al2O3. As a result of observation using a scanning electron microscope (manufactured by Hitachi High-Tech Corporation, SU8220), the number of resin particles forming the protrusions was 10 per unit predetermined area (100 μm×100 μm).

[0060] [Preparation of electrolyte]

[0061] To 100 parts by mass of a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7, 5 parts by mass of vinylene carbonate (VC) was added, and lithium hexafluorophosphate (LiPF6) was dissolved in the resulting solution at a concentration of 1.5 mol / L, thereby preparing an electrolyte solution.

[0062] [Manufacturing of secondary batteries]

[0063] The positive electrode and the negative electrode are wound into a spiral shape with a separator sandwiched therebetween to produce a wound electrode body. At this time, the filler layer of the separator is placed opposite to the positive electrode. Insulating plates are arranged above and below the above-mentioned electrode body, and the electrode body is housed in an outer packaging can. The negative electrode lead is welded to the bottom of the outer packaging can with a bottomed cylindrical shape, and the positive electrode lead is welded to the sealing body. After injecting the electrolyte into the outer packaging can, the opening of the outer packaging can is sealed with a sealing body with a gasket sandwiched therebetween, and a non-aqueous electrolyte secondary battery is produced by standing in a constant temperature bath at 60°C for 15 hours. The capacity of the secondary battery produced is 4600mAh.

[0064] [Evaluation of liquid permeability]

[0065] When injecting electrolyte into the outer can during the production of the secondary battery, the liquid permeability is evaluated. The time from the injection of electrolyte from the opening of the battery to the time when the electrolyte remaining on the upper part of the electrode body penetrates into the electrode body and disappears visually is measured, and this time is used as the index of liquid permeability.

[0066] [Evaluation of plate deformation]

[0067] The secondary battery was charged at a constant current of 1380mA (0.3It) until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 92mA (0.02It). Thereafter, the battery was discharged at a constant current of 4600mA (1.0It) until the battery voltage reached 2.7V. This charge and discharge cycle was repeated for 500 cycles with a rest period of 20 minutes inserted between each cycle. After 500 cycles, the non-aqueous electrolyte secondary battery was charged at a constant current of 1380mA (0.3It) until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 92mA (0.02It) to set the battery to a charged state. The non-aqueous electrolyte secondary battery in the charged state was subjected to cross-sectional observation near the winding center of the electrode body using an X-ray CT device (manufactured by Shimadzu Corporation, SMX-225CT FPD HR). As Figure 3 As shown, when deformation (bending) of the electrode plate (at least one of the positive electrode and the negative electrode) was confirmed at an angle θ of 150° or less, it was determined that the electrode plate was deformed and the electrode plate deformation was evaluated.

[0068] <Example 2>

[0069] A secondary battery was produced and evaluated in the same manner as in Example 1, except that the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles in the preparation of the separator was changed to 3 parts by mass. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 18.

[0070] <Example 3>

[0071] A secondary battery was produced and evaluated in the same manner as in Example 1 except that the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles was changed to 6 parts by mass in the preparation of the separator. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 35.

[0072] <Example 4>

[0073] A secondary battery was produced and evaluated in the same manner as in Example 1, except that acrylic resin particles with a D50 of 6 μm were used instead of acrylic resin particles with a D50 of 4 μm in the preparation of the spacer, and the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles was changed to 5 parts by mass. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 25.

[0074] <Comparative Example 1>

[0075] A secondary battery was produced and evaluated in the same manner as in Example 1, except that acrylic resin particles with a D50 of 6 μm were used instead of acrylic resin particles with a D50 of 4 μm in the preparation of the spacer, and the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles was changed to 3 parts by mass. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 5.

[0076] <Comparative Example 2>

[0077] A secondary battery was produced and evaluated in the same manner as in Example 1, except that acrylic resin particles with a D50 of 1 μm were used instead of acrylic resin particles with a D50 of 4 μm in the preparation of the spacer, and the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles was changed to 2 parts by mass. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 8.

[0078] <Comparative Example 3>

[0079] A secondary battery was produced and evaluated in the same manner as in Example 1 except that the mixing ratio of acrylic resin particles to 100 parts by mass of α-Al2O3 particles in the preparation of the separator was changed to 10 parts by mass. As a result of SEM observation, the number of resin particles forming the convex portion per unit predetermined area (100 μm×100 μm) was 46.

[0080] The evaluation results of the secondary batteries of the examples and comparative examples are shown in Table 1. The liquid permeability is expressed as a relative value with the time when the standard spacer is used being 100. In addition, Table 1 also shows the D50 of the acrylic resin particles, the mixing ratio of the acrylic resin particles to 100 parts by mass of the α-Al2O3 particles, and the number of resin particles forming the convex portions per unit area (100 μm×100 μm).

[0081]

[0082] The secondary batteries of the examples did not show plate deformation, and the liquid permeability was good. On the other hand, the secondary batteries of Comparative Examples 1 and 2 showed plate deformation, and the liquid permeability of the secondary battery of Comparative Example 3 was poor. It can be seen that by including resin particles in the filler layer so that the number of resin particles forming the convex portion per unit area (100 μm×100 μm) is 10 to 35, the liquid permeability is improved while suppressing plate deformation.

[0083] The present invention can be further described by the following embodiments.

[0084] Composition 1:

[0085] A non-aqueous electrolyte secondary battery comprises an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, an electrolyte, and an outer packaging can for accommodating the electrode body and the electrolyte.

[0086] The spacer comprises a base material layer and a filler layer formed on at least one surface of the base material layer.

[0087] The filler layer includes inorganic particles and resin particles having a larger particle size than the inorganic particles, and has convex portions formed by the resin particles.

[0088] The convex portions protrude from an inorganic particle layer, which is a layer of the filler layer other than the convex portions and formed of the inorganic particles.

[0089] When the surface of the filler layer is observed with a scanning electron microscope, 10 to 35 of the resin particles forming the projections are detected in a region of 100 μm×100 μm.

[0090] Composition 2:

[0091] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein an average particle diameter of the resin particles is larger than a thickness of the inorganic particle layer by 1 μm to 10 μm.

[0092] Composition 3:

[0093] The nonaqueous electrolyte secondary battery according to configuration 1 or 2, wherein the inorganic particles are in contact with the substrate layer.

[0094] Composition 4:

[0095] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the resin particles are bonded to the positive electrode.

[0096] Description of Reference Numerals

[0097] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 13a base material layer, 13b filler layer, 14 electrode body, 15 outer can, 16 sealing body, 17, 18 insulating plate, 19 positive electrode lead, 20 negative electrode lead, 21 slotted portion, 22 filter, 23 lower valve body, 24 insulating member, 25 upper valve body, 26 cover, 26a opening, 27 gasket, 30 inorganic particles, 32 resin particles, 34 inorganic particle layer.

Claims

1. A non-aqueous electrolyte secondary battery, The invention comprises an electrode body in which a positive electrode and a negative electrode are wound with a separator interposed therebetween, an electrolyte, and an outer packaging tank for accommodating the electrode body and the electrolyte. The spacer comprises a base material layer and a filler layer formed on at least one surface of the base material layer. The filler layer includes inorganic particles and resin particles having an average particle size larger than that of the inorganic particles, and has convex portions formed by the resin particles. The convex portions protrude from an inorganic particle layer, and the inorganic particle layer is a layer of the filler layer other than the convex portions and formed of the inorganic particles. When the surface of the filler layer was observed with a scanning electron microscope, 10 to 35 of the resin particles forming the protrusions were detected in a region of 100 μm×100 μm.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The average particle diameter of the resin particles is larger than the thickness of the inorganic particle layer by 1 μm to 10 μm.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The inorganic particles are in contact with the substrate layer.

4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The resin particles are bonded to the positive electrode.